Complete mitochondrial genome analysis of Japanese Spanish mackerel (Scomberomorus niphonius) with phylogenetic consideration. Issue 1 (1st January 2017) - Jin, Yan; Ouyang, Longling; Zheng, Hongxiang; Lin, Yu; Zhang, Menghan; Li, Shengfa; Cheng, Jiahua
Abstract: The complete mitochondrial DNA (mtDNA) of Japanese Spanish mackerel ( Scomberomorus niphonius ) was cloned and sequenced. The total length of the mitochondrial genome is 16, 646 bp with an accession number KY228987. Thirty-seven genes are identified in total, including 13 protein-coding genes, 22 transfer RNA (tRNA) genes, 2 ribosomal RNA (rRNA) genes and a putative D-loop region. Among these genes, 9 are encoded on the light strand, while others are encoded on the heavy strand. The overall base composition of mitogenome is 28.39% for A, 16.14% for G, 26.52% for T, 28.96% for C, respectively, with a slight higher A + T content (54.91%). The phylogeny analysis based on 18 COI amino acid sequences suggested that S . niphonius and the other two species from Scomberomorus (Scombridae) formed a cluster apart from the one comprising other genus from Scombridae. The complete mitogenome may shed light on the future study of genetic mechanism of Scomberomorus niphonius .